DEVELANDO EL ENFOQUE TEÓRICO EN LAS INTERVENCIONES DEL PATRIMONIO EDIFICADO VIRREINAL DEL CUSCO: REFLEXIONES EN TORNO A LA RESTAURACIÓN DE LA CASA CONCHA - Usca Baca, Alex Iván (2017)
This article tries to analyze the apparent insufficiency of theoretical criteria or approaches used in the restor- ative processes of Cusco’s vice regal architecture carried out in the last fifteen years. In charge of such an activity, the Peruvian State, through today’s Culture Ministry of Cusco, played a preponderant role. The present paper takes as case-study the restoration and revaluation of the Concha House. They were exceptional among the in- terventions carried out by the State, which was mostly dedicated to intervene religious building heritage (Cath- olic temples and chapels). In order to do this, the structure proposed by Josep María Montaner (1999) has been used. Initially, it attempts to contextualize, from the historical and architectural points of view, the main events (milestones) that marked the restorative process in the Cusco area, until we arrive to the intervention of Concha House. Through a comparative analysis, it tries to unveil the theoretical and/or methodological approaches used; to then carry out the formal analysis of the edifice after its intervention. Finally, it proposes the possible motives and management mechanisms that propelled the process to its longed-for social appropriation.